Testing Alternative Hypotheses Regarding the Association Between Behavioral Inhibition and Language Development in Toddlerhood. Issue 4 (5th February 2014) - Smith Watts, Ashley K.; Patel, Deepika; Corley, Robin P.; Friedman, Naomi P.; Hewitt, John K.; Robinson, JoAnn L.; Rhee, Soo H.
<x xml:space="preserve">Abstract</x> Studies have reported an inverse association between language development and behavioral inhibition or shyness across childhood, but the direction of this association remains unclear. This study tested alternative hypotheses regarding this association in a large sample of toddlers. Data on behavioral inhibition and expressive and receptive language abilities were collected from 816 twins at ages 14, 20, and 24 months. Growth and regression models were fit to the data to assess the longitudinal associations between behavioral inhibition and language development from 14 to 24 months. Overall, there were significant associations between behavioral inhibition and expressive language, and minimal associations with receptive language, indicating that the association is better explained by reticence to respond rather than deficient language development.